A Review of the Applications of Dual-Energy CT in Acute Neuroimaging. Issue 3 (August 2020) - Gibney, Brian; Redmond, Ciaran E.; Byrne, Danielle; Mathur, Shobhit; Murray, Nicolas
Dual-energy computed tomography (CT) is a promising tool with increasing availability and multiple emerging and established clinical applications in neuroradiology. With its ability to allow characterization of materials based on their differential attenuation when imaged at two different energy levels, dual-energy CT can help identify the composition of brain, neck, and spinal components. Virtual monoenergetic imaging allows a range of simulated single energy-level reconstructions to be created with postprocessing. Low-energy reconstructions can aid identification of edema, ischemia, and subtle lesions due to increased soft tissue contrast as well as increasing contrast-to-noise ratios on angiographic imaging. Higher energy reconstructions can reduce image artifact from dental amalgam, aneurysm clips and coils, spinal hardware, dense contrast, and dense bones. Differentiating iodine from hemorrhage may help guide management of patients after thrombectomy and aid diagnosis of enhancing tumors within parenchymal hemorrhages. Iodine quantification may predict hematoma expansion in aneurysmal bleeds and outcomes in traumatic brain injury. Calcium and bone subtraction can be used to distinguish hemorrhage from brain parenchymal mineralization as well as improving visualization of extra-axial lesions and vessels adjacent to dense plaque or skull. This article reviews the basics of dual-energy CT and highlights many of its clinical applications in the evaluation of acute neurological presentations.